Vertebrae Cervical of Egret (Egretta garzeta) - Haqiqi, Nila ‘Uyun; Rini, Pradita Icha Listya; Krismiati, Ririn (Proceeding International Conference on Science and Engineering, 2020)
Egret is a long-necked bird that is often found in several regions in Indonesia. Egret have different neck bone structure than the other birds. When flying position the neck can be folded to from the letter S and when taking food the neck can bend down unt il it reaches the ground surface. His neck is strong and cannot be broken. Egret’s neck is composed of 13 vertebrae, each of which has a different structure and functions. In sections C5 to C7 have special characteristics. The sixth neck bone lengthens and the arrangement of muscle connections is elastic. To observe the cervical vertebrae in Egret done by cleaning all attached tissue then observed using a binocular stereo microscope wurh a magnification of 0.8x. The observations show that at C5 it has a longer segment than the others and has posterior condyle. Then in C6 there is a pivot point that allows the Egret to pull their necks into an S shape and allows Egret to push the head forward and catch prey at high speed (Wheler, 1929)